The Transformation of Islamic Education in the Formation of the Cultural Identity of the Archipelago: A Comparative Study of Indonesia and Brunei Darussalam - Hidayat (Proceedings: International Seminar On Educational Studies, 2025)
The transformation of Islamic education in the Nusantara region holds a vital role in preserving the continuity of Malay-Islamic cultural values. This study aims to analyze the role of Islamic education in shaping cultural identity in Indonesia and Brunei Darussalam as representations of the heritage of Islamic Civilization in the Malay Archipelago. The research employs a descriptive qualitative approach through literature analysis and a comparative study of educational policies, curricula, and Islamic value orientations in both countries. Data were collected from primary and secondary sources, including official documents, scholarly articles, and recent research findings. The analysis reveals that Islamic education in Indonesia is oriented toward religious moderation, cultural adaptation, and multiculturalism, while Islamic education in Brunei Darussalam emphasizes the Malay Islamic Monarchy ideology, which upholds loyalty and moral integrity. These differences have resulted in two distinct models of Islamic education that both preserve the values of Islamic civilization within their respective social contexts. The integration of religion, culture, and educational policy demonstrates that Islamic education plays a strategic role in strengthening the cultural identity of the Nusantara. This study contributes to a deeper understanding of the continuity of Islamic Civilization in Southeast Asia and its relevance in addressing the challenges of educational globalization.